2011
DOI: 10.1111/j.1755-3768.2011.02110.x
|View full text |Cite
|
Sign up to set email alerts
|

Favourable outcome after cataract surgery with IOL implantation in uveitis associated with juvenile idiopathic arthritis

Abstract: ABSTRACT.Purpose: Management of uveitic cataract in patients with juvenile idiopathic arthritis (JIA) is challenging, and intraocular lens (IOL) implantation is controversial. This study investigated the outcome after minimally invasive surgery with IOL implantation. Methods: Retrospective analysis after phacoemulsification with in-the-bag IOL implantation was performed in 16 patients (17 operations) with ANA-positive JIAassociated chronic uveitis. In these patients, 25 G capsulectomy and anterior vitrectomy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 24 publications
2
42
0
7
Order By: Relevance
“…Removal of the lens by phacoemulsification is the usual surgical treatment for a cataract that is impacting significantly on visual acuity [72]. Complete control of intraocular inflammation for at least 3 months prior to surgery is associated with improved outcomes [73,74]. Aggressive Case series (n = 3) and case report showing efficacy.…”
Section: Surgical Treatmentsmentioning
confidence: 99%
“…Removal of the lens by phacoemulsification is the usual surgical treatment for a cataract that is impacting significantly on visual acuity [72]. Complete control of intraocular inflammation for at least 3 months prior to surgery is associated with improved outcomes [73,74]. Aggressive Case series (n = 3) and case report showing efficacy.…”
Section: Surgical Treatmentsmentioning
confidence: 99%
“…Although the IOL implantation has been controversial, there is increasing evidence that this is a safe procedure with current surgical techniques. 112 However…”
Section: ; 109mentioning
confidence: 99%
“…The two most recent studies of JIA-associated uveitis 19,20 confirmed the requirement of maximum perioperative control of inflammation without an increased risk for ocular complications.…”
Section: Discussionmentioning
confidence: 84%